Analysis Of Optimising Cooperative Performance Through Digital-Based Reporting Management System - Suandana, Ni Putu Widantari; Sandhiyasa, I Made Subrata; Aditama, Putu Wirayudi; Adnyana, I Nyoman Widhi (Jurnal Scientia, 2024)
This research aims to examine the optimization of Cooperative performance through a digital-based reporting management system. The case study method is used to analyze user needs and design relevant system features. The needs analysis is useful in identifying constraints and needs in the current reporting system. Based on this analysis, features such as interactive dashboards, real-time reporting, digital financial management, and member management were designed and tested. The results show an increase in operational efficiency, transparency, and accountability of the cooperative. The implementation of this system successfully met user needs and improved the cooperative's performance